Управління талантами як складник інтелектуального капіталу підприємства в умовах інтелектуалізації економіки - Драган, Олена Іванівна (My University, 2020)
Стаття присвячена дослідженню в галузі інтелектуального капіталу та управління талантами компаній. Простежується пряма залежність між розвитком інтелектуального капіталу підприємства та ефективним управлінням талантами, яке забезпечує його зростання. Обґрунтовано існуючий тісний зв’язок між концепціями «інтелектуальний капітал» і «управління талантами» за рахунок спорідненості процесів і виконання поставлених завдань. Узагальнені підходи, які застосовуються для розвитку інтелектуального капіталу у системі управління талантами підприємства. Проаналізовані основні складові системи управління талантами: оцінка талантів, коучинг, наставництво, планування спадкоємності. Досліджені переваги та недоліки підходів для забезпечення топ-посад талановитими співробітниками: залучення успішних фахівців із інших компаній-конкурентів; «вирощування» власних талантів всередині організації. Запропоновано методичне забезпечення розвитку управління талантами як складника інтелектуального капіталу підприємства. The article is devoted to the research in the industry of intellectual capital and management of companies’ talents. Foreign experience of providing competitiveness of well-known companies testifies about its dependence on intellectualization and unicity of knowledge of the most talented workers with the help of whom the income is increased. Direct dependence between the development of intellectual capital of the enterprise and effective management of talents that provide its increase. In the context of human capital, an intellectual capital presents its constituent that constantly develops due to new knowledge, work, creativity, intellectual thinking, intellectual activity for forming new ideas, inventions. The most successfully intellectual capital can be developed in the process of new products creation, innovations, when it is needed to concentrate informative, intellectual, material and financial resources. At the same time, exactly talented workers give an opportunity to get the intellectual product of activity that is distinguished by a novelty, unicity, creativity, high level of perfection. The existed close connection between conceptions “intellectual capital” and “management talents” due to the cognation of processes and implementation of given tasks is described. Generalized approaches that are used for the development of intellectual capital in control system by talents of the enterprise. Basic component of control system by talents, such as: estimation of talents, coaching, tutorship, planning of succession is analyzed. Advantages and disadvantages of approaches for providing top-position by talented employees: hiring successful specialists from other companies-competitors; “growing” of own talents inside the organization are investigated. The methodical application of management talents development as a constituent of intellectual capital of the enterprise is offered. The pyramid of dependence of talent management on the general concepts is offered: personnel management, knowledge management, creative management, human capital and intellectual capital.
Keywords: інтелектуальний капітал; управління талантами; розвиток; концепція; інтелектуалізація; знання; персонал; intellectual capital; management; development; conception; intellectualization; knowledge; personnel; кафедра економіки праці та менеджменту